Interleukin-18 and IL-18BP in inflammatory dermatological diseases - Wang, Xiaoyun; Wang, Lian; Wen, Xiang; Zhang, Lu; Jiang, Xian; He, Gu (Frontiers in Immunology, 2023)
IL-18 belongs to the IL-1 family of pleiotropic pro-inflammatory factors, and IL-18BP is a native antagonist of IL-18 in vivo, regulating its activity. Moreover, IL-18 exerts an influential function in host innate and adaptive immunity, and IL-18BP has elevated levels of INF-γ in diverse cells, suggesting that IL-18BP is a negative feedback inhibitor of IL-18-mediated immunity. Similar to IL-1, the IL-18 cytokine is produced as an indolent precursor that requires further processing into an active cytokine by caspase-1 and mediating downstream signaling pathways through MyD88. IL-18 has been implicated to play a role in psoriasis, atopic dermatitis, rosacea, and bullous pemphigoid in human inflammatory skin diseases. Currently, IL-18BP is less explored in treating inflammatory skin diseases, while IL-18BP is being tested in clinical trials for other diseases. Thereby, IL-18BP is a prospective therapeutic target.